Indications of Dynamic Effects on Scaling Relationships Between Channel Sinuosity and Vegetation Patch Size Across a Salt Marsh Platform. Issue 10 (29th October 2018) - Taramelli, Andrea; Valentini, Emiliana; Cornacchia, Loreta; Monbaliu, Jaak; Sabbe, Koen
Abstract: Salt marshes are important coastal areas that consist of a vegetated intertidal marsh platform and a drainage network of tidal channels. How salt marshes and their drainage networks develop is not fully understood, but it has been shown that the biogeomorphic interactions and feedbacks between vegetation development and channel formation play an important role. We examined the relationships among tidal channel sinuosity, marsh roughness, vegetation type (pioneer, Elymus athericus or Phragmites australis ), and patch size at different spatial scales using a high‐resolution vegetation map (derived from aerial photography) and lower‐resolution satellite imagery processed with linear spectral mixture analysis. The patch‐size distribution in all vegetation types corresponded to a power law, suggesting the presence of self‐organizational processes. While small vegetation patches are more dominant in pioneer vegetation, they were present in all vegetation types. The largest patch size is restricted to E. athericus . We observed an inverse logarithmic relationship between channel sinuosity and vegetation patch size in all vegetation types. The fact that this relationship is observed in both pioneer and later successional stages suggests that after the establishment of a drainage network in the dynamic pioneer stages of salt marsh development, the later stages of salt marsh succession largely inherit the meandering pattern of the early successional stages. Our study confirms recent evidence that no significant changes in the specific features of tidal channel networks (e.g., channel width, drainage density, and efficiency) take place during the later stages of salt marsh development. Key Points: The imprint of biogeomorphic processes on salt marsh drainage network sinuosity during the pioneer stages is inherited by later successional vegetation types Vegetation patch‐size distributions in salt marsh vegetations from the pioneer to late successional stages correspond to power laws, suggesting the presence of self‐organizational processes Vegetation patch size in salt marshes shows an inverse logarithmic relationship with tidal channel sinuosity, irrespective of vegetation type and elevation